Limnological aspects of humic substances in Chubut River (Patagonia-Argentina) - Scapini, M. del C. (2011)
Humic Substances (HSs) of the Chubut River (Patagonia-Argentina) have been investigated, during two consecutive years and different climatic seasons, in order to obtain a first approach at their spatial and temporal distribution, as well as their origin and relation with environmental characteristics. Absorbance at 250 nm and limnological variables were measured and the data processed by different statistical tools. We found that the processes developed in the lower sections of Chubut River are dominated by those produced in the Florentino Ameghino Reservoir. The riverine HSs are present in very low concentrations, have mainly autochthonous origin, exhibit spatial homogeneity and temporal variability similar to nutrients (nitrates and soluble reactive phosphorus).